EVALUASI SUHU AWAL PENYEDUHAN TERHADAP KARAKTERISTIK FISIKOKIMIA DAN SENSORIS TEH SERAI WANGI (Cymbopogon nardus L.) PRODUKSI PT. KARSA ABADI - Praba Sari, Ida Ayu Gede Satwika Candra; Wrasiati, Luh Putu; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Herbal tea is a tea that is not made from tea leaves ( Cameliia sinensis ) but is made from raw materials of flowers, leaves, seeds, roots or dried fruits that are usually healthy and don’t contain caffeine. One of the ingredients used in making herbal tea is lemongrass. The purpose of this study is to determine the effect of the initial temperature of brewing on the physicochemical and sensory characteristics of lemongrass tea and determine the initial temperature of brewing in producing lemongrass tea with the best physicochemical and sensory characteristics. The initial temperature of brewing which consists of five levels, namely 60ºC, 70ºC, 80ºC, 90ºC and 100ºC. The results showed that the initial brewing temperature treatment greatly affected the physicochemical and organoleptic characteristics. The higher the initial brewing temperature treatment, the resulting lemongrass tea with the best physicochemical and organoleptic characteristics, the initial temperature treatment of brewing 100ºC resulted in a total phenolic characteristic of 0.46±0.02 mg GAE/g, IC50 antioxidant activity of 6,610.13±90.53 ppm, water soluble essence of 10.32%.  brightness level (L*) 14.56±0.18, reddish level (a*) 8.89±0.19, yellowish level (b*) 12.00±0.37. The best products selected from the sensory assessment were with a color score of 3.1±0.64 (yellowish green), a taste score of 3.6±0.75 (slightly bitter), a scent scoring of 4.2±0.77 (lemongrass-scented), and an overall reception of 5.65±1.14 (somewhat like).